Health outcomes and socio-economic status among the elderly in China: Evidence from the CHARLS pilot - John Srauss; Xiaoyan Lei; Albert Park; Yan Shen; James P. Smith (Institute for the Study of Labor (IZA), 2010)
We are concerned in this paper with measuring health outcomes among the elderly in Zhejiang and Gansu provinces, China, and examining the relationships between different dimensions of health status and measures of socio-economic status (SES). We use the China Health and Retirement Longitudinal Study (CHARLS) pilot data to document health conditions among the elderly in Gansu and Zhejiang provinces, where the survey was fielded. We use a very rich set of health indicators that include both self-reported measures and biomarkers. We also examine correlations between these health outcomes and two important indicators of socioeconomic status (SES): education and log of per capita expenditure (log pce), our preferred measure of household resources. While there exists a very large literature that examines the relationships between SES and health measures, little has been done on Chinese data to see whether correlations reported in many other countries are replicated in China, particularly so for the aged. In general education tends to be positively correlated with better health outcomes, as it is in other countries. However, unmeasured community influences turn out to be highly important, much more so than one usually finds in other countries. While it is not yet clear which aspects of communities matter and why they matter, we set up an agenda for future research on this topic. We also find a large degree of under-diagnosis of hypertension, a major health problems that afflicts the aged. This implies that the current health system is not well prepared to address the rapid aging of the Chinese population, at least not in Gansu and Zhejiang.
Keywords: I10; 330; health; China; Gesundheit; Alte Menschen; Soziale Lage; China; Gansu; Zhejiang